2001
DOI: 10.1038/sj.mp.4000856
|View full text |Cite
|
Sign up to set email alerts
|

Association between violent suicidal behavior and the low activity allele of the serotonin transporter gene

Abstract: There is compelling evidence that serotonin system dysfunction is associated with certain behavioral disorders, such as suicidal behavior and impulsive aggression. A functional polymorphism in the promoter region of the serotonin transporter gene (5-HTTLPR) was recently identified and the presence of the short allele found to be associated with a lower level of expression of the gene, lower levels of 5-HT uptake, suicidal behavior and anxiety-related traits. We genotyped 51 West European Caucasians who had mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
1
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(84 citation statements)
references
References 25 publications
7
74
1
2
Order By: Relevance
“…Indeed, it has been reported that SSRIs induce AIM in a dose-dependent manner. 12 Several independent associations have been reported between the 's' allele and anxiety disorders, violent suicidal behavior, [13][14][15] seasonal affective disorder 16 and rapid cycling (this study). These results, together with the association reported by Mundo et al 8 and the association between the 's' allele and rapid cycling (this study), suggest that there is an association between the 5-HTTLPR 's' allele and a pattern of affective instability.…”
Section: -Htt Gene and Antidepressant-induced Maniamentioning
confidence: 61%
“…Indeed, it has been reported that SSRIs induce AIM in a dose-dependent manner. 12 Several independent associations have been reported between the 's' allele and anxiety disorders, violent suicidal behavior, [13][14][15] seasonal affective disorder 16 and rapid cycling (this study). These results, together with the association reported by Mundo et al 8 and the association between the 's' allele and rapid cycling (this study), suggest that there is an association between the 5-HTTLPR 's' allele and a pattern of affective instability.…”
Section: -Htt Gene and Antidepressant-induced Maniamentioning
confidence: 61%
“…This finding was supported by another group who found that subjects with the ll genotype had significantly higher scores on Beck's Hopelessness Scale and Beck's Scale for Suicide Ideation than subjects with either the ls or ss genotype (Russ et al, 2000). In contrast, three other groups of researchers observed an association between the s allele and violent suicidal behavior, while a fourth found a link between the s allele and the number of lifetime suicide attempts and lethality of the suicidal behavior (Bellivier et al, 2000;Bondy et al, 2000;Gorwood et al, 2000;Courtet et al, 2001).…”
Section: Genetics Of Sertmentioning
confidence: 83%
“…Seven of these studies failed to demonstrate any link between suicidal behavior and SERT genotype or 5-HTTLPR allele frequency (Ohara et al, 1998;Chong et al, 2000;Geijer et al, 2000;Ho et al, 2000;Mann et al, 2000;Fitch et al, 2001;Rujescu et al, 2001). The remaining seven studies all found some association, albeit with differing results (Du et al, 1999;Bellivier et al, 2000;Bondy et al, 2000;Gorwood et al, 2000;Russ et al, 2000;Courtet et al, 2001;Baca-Garcia et al, 2002). One study demonstrated a higher frequency of the l allele in depressed suicide victims compared to nonsuicidal controls (Du et al, 1999).…”
Section: Genetics Of Sertmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] These polymorphisms and a 3ЈUTR SNP have been studied in several neuropsychiatric disorders and personality quantitative trait loci (QTLs), including response to antidepressant treatment. [21][22][23][24] A series of transmission/disequilibrium test (TDT) studies using 5-HTTLPR and VNTR to determine whether SLC6A4 contributes to susceptibility to autistic disorder failed to reveal any consistent evidence of transmission of an allele or haplotype. [25][26][27][28][29][30] Using the TDT, evidence of preferential transmission of the short variant of 5-HTTLPR was found by Cook and colleagues 25 and preferential transmission of the long allele was reported by others.…”
Section: Introductionmentioning
confidence: 99%